Organization Branding in the Post-COVID-19 World – An Employer and Employee Perspective - Mishra, Monu Pandey; Mishra, Vinaytosh (Indian Journal of Marketing, 2023)
Employer branding is a tool to create a positive perception of an organization in the minds of existing and prospective employees. Employer branding not only helps in getting the best talent for an organization, but also reduces the cost of talent acquisition. Employees are not merely passive participants of the recruitment process; they aggressively seek information about the employers using secondary resources like blogs and social media pages of the company and are involved in the co-creation of the recruitment process. The study used a narrative review to identify the factors affecting employer branding. The study then used the multi-criteria decision making (MCDM) technique and TOPSIS to rank these factors, hence identifying the importance of five factors for an employer. The study further performed conjoint analysis to identify the utility of the identified factors for employees. The narrative review of the studies identified salary, job security, training and development, work-life balance, and career progress. The study's results suggested a significant gap between employers' and employees' perspectives, which must be addressed. Salary and job security are the hygiene factors and had a high priority for employees and employers. While career progress is important for employees, it got less preference from employers. The study findings will be useful for managers designing online branding strategies and those at the helm of corporate communication.